PERFORMANCE ASSESSMENT ANALYSIS USING MALCOLM BALDRIGE CRITERIA FOR PERFORMANCE EXELLENCE (MBCfPE) METHOD (Case Study at PT. NYCZ) - Mohammad Rachman Waluyo; Nurfajriah Nurfajriah; Alina Cynthia Dewi; Clarissa Vadya Azarine (Center for Study and Journal Management FTI UMI, 2021)
PT. NYCZ is a manufacturing company engaged in plastic bottle packaging production that cannot be separated from the problem of competition with similar companies. The problems encountered at PT. NYCZ regarding employee performance, namely lack of communication relations between subordinates and superiors, so that delivery of work instructions from superiors is still not understood by subordinates, it has an impact on employee performance output, Therefore the company must improve more efficient strategies in terms of leadership that is able to run and manage everything in internal and external of the company, more reliable skilled workforces, modern machines and technology, and is able to get a wider market and customers in plastic bottle products marketing. Malcolm Baldrige Criteria for Performance Excellence or Baldrige Criteria is a guide for a company to achieve high quality performance which consists 7 criterias, namely Leadership; Strategic Planning; Customer Focus; Measurement, Analysis and Knowledge Management; Focus on Workforce; Process Management; and Results. This research was conducted by distributing questionnaires to PT. NYCZ employees, respondents were taken according to job desks ranging from cashiers to managers. After questionnaire data was obtained, it was processed using SPSS to test validity and reliability. Then, questionnaire results were processed using Malcolm Baldrige score to determine company performance level. From the research results, it was obtained that the total points from Malcolm Baldrige Criteria for Performance Excellence survey are 411,14. Therefore, according to MBCfPE score, the performance of PT. NYCZ is Early Improvement with Average category